Acid catalyst influence on the polymerization time of polyfurfuryl alcohol and on the porosity of monolithic vitreous carbon - Origo, Fábio Dondeo; Arisseto, Júlia Cassiano; Seixas, Fernanda Lini; Miyakawa, Walter; Damião, Alvaro José; Oishi, Sílvia Sizuka [UNESP]; Botelho, Edson Cocchieri [UNESP] (Wiley, 2016)
This study compares the influence of different acid catalysts on the polymerization rate of polyfurfuryl alcohol (PFA) precursor and especially on the respective porosity of Monolithic Vitreous Carbon (MVC) produced from that. Five acid catalysts commonly used were compared: p-toluenesulfonic (PTLS), hydrochloric, sulfuric, nitric, and phosphoric. A fixed molar concentration of catalyst was diluted in PFA resin under room pressure and temperature. The time dependence of PFA resin polymerization was investigated by optical transmittance of PFA films, and the polymerization degree, characterized by ATR spectroscopy and thermogravimetry. MVC samples prepared with the same PFA resin and each catalyst were carbonized up to 1200 °C, under inert atmosphere. MVC porosity was studied by nitrogen adsorption/desorption, and by SEM and optical microscopy. Higher polymerization degree and higher residual mass were obtained with faster catalysts. No direct relation between the polymerization rate and the acid force was observed. PTLS promoted the fastest PFA polymerization process and the sulfuric acid, the slowest one. MVC samples were obtained by slow carbonization. MVC presented low specific surface SBET from 1.4 to 7.4 m2/g. Nitric acid catalyst contributed the most to micropores formation. Micrometric apparent porosity was smaller for the catalysts having longer polymerizations times, such as phosphoric and sulfuric acid. Phosphoric catalyst corresponded to the lowest porosity in MVC. As the polymerization time increased, the average size of the micrometric surface pores tended to augment. The MVC macroscopic porosity increased with the SBET increment. Acid catalysts choice exerted a fundamental role on the porosity of MVC.
Keywords: catalysts; microscopy; porous materials; resins; synthesis and processing